Analysis of Weaving Design and Symbols of Traditional Weaving Cloth in Koting - Naro, *Antonius Maria K.; Yunarti, Herlina; Mayaputri, Velmi (Riwayat: Educational Journal of History and Humanities, 2022)
This research aims to identify and analyze the meaning contained in the types of designs and symbols on weaving cloth, especially for women in Koting village. The research used qualitative methods. Data collection techniques used in this research are observation, interview, and study documentation. The results of the analysis found several types of weaving, with the types of designs such as geometric design, nature design and combination design. In addition, it was found several types of symbols such as lines, forms and colors. The researcher concludes that the overall meaning contained in weaving cloth is self-esteem and a reflection of the goodness of a woman such as loving, protecting, respecting in a family and others.